PEMANFAATAN SAMPAH PLASTIK MENJADI BRIKET SEBAGAI BAHAN BAKAR ALTERNATIF DALAM KILN DI PABRIK PT SEMEN PADANG - Hendri Sawir (Sekolah Tinggi Teknologi Industri Padang, 2016)
Coal is a natural resource that can not be updated and will be depleted when used continuously. PT Semen Padang is a cement industries that use coal as fuel in large quantities which can increase production costs. It should be considered for alternative materials that can be used as fuel. The example is plastic waste that has tremendous potential as an alternative fuel. For that conducted research on the make of plastic waste into briquettes with technology Plastic Waste as alternative fuel to substitute for coal in the kiln PT Semen Padang from two types of plastic waste, is garbage plastic bags (PP) and a glass of mineral water plastic waste (PET). This study aims to determine the quality of briquettes, to obtain a picture of whether plastic pellets briquettes can be used as a substitute for coal and a comparison of the use of coal briquettes plastic pellets in the kiln PT Semen Padang. From the test, it is known that the briquettes garbage plastic bags have a calorific value of 10.112 cal/gram, ash content of 3,90%, 0,36% moisture and volatile content of 94,74%. And briquettes from waste plastic glasses of mineral water has a calorific value of 10.844 cal/gram, ash content of 0,27%, 0,42% moisture and volatile content of 99,27%. From these results it can be seen that the briquettes from waste glasses of mineral water has a better quality. And when compared with the specifications of coal used in the kiln Indarung IV calorific value 5200 - 5600 cal/gram, maximum ash content of 20% and a maximum water content of 10%, then the two types of briquette plastic pellets can be used as a fuel substitute for coal. Based on the comparison of calorific value and the use of coal in the kiln Indarung IV which is an average of 35 tons / hour, then the ratio of the amount of usage of coal with briquettes from waste plastic bags is 1: 0.53, and with briquettes from waste plastic glasses of mineral water is 1: 0.50. Keywords: plastic waste, coal, briquettes, quality, fuel